Government spending efficiency, measurement and applications : a cross-country efficiency dataset - Afonso, António (2020)
This chapter conducts a review of the literature dealing with overall public sector performance and efficiency, it defines a methodology to assess public sector efficiency and it creates a novel and large cross-sectional panel dataset of government indicators and public sector efficiency scores. The focus is on a balanced sample covering all 36 OECD countries over the time period between 2006 and 2017. First, we define a set of economic and sociodemographic metrics necessary to construct performance composite indicators. Second, we calculate and report a full set of (input and output oriented) efficiency scores based on the performance indicators previously computed.